TINJAUAN METODOLOGI INDOMATH STUDY - Sutarto Hadi (Universitas Negeri Yogyakarta, 2003)
Abstract This paper discusses the various aspects of development research activities in the IndoMath Study. This study was developed along lines of formative research: orientation, design and evaluation of intervention, and evaluation of its effectiveness. The research has been conducted during the three fieldworks Yogyakarta. In the first and second fieldwork, the focus was mainly on the design and evaluation of adapted RME exemplary curriculum materials as well as in-service education program. In the third fieldwork, the focus was on the effectiveness of intervention to introduce Realistic Mathematic Education (RME) to mathematic teachers. Keywords: formative research, development research, indomath study